MR imaging in multiple sclerosis: comparison with clinical, CSF, and visual evoked potential findings. - Uhlenbrock, D; Seidel, D; Gehlen, W; Beyer, H K; Haan, J; Dickmann, E; Zeit, T; Herbe, E (American Journal of Neuroradiology, 1988)
MR examinations of 136 patients with multiple sclerosis (MS) were evaluated to correlate the results with clinical, CSF, and visual evoked potential (VEP) findings. In addition, 22 of the 136 patients were studied several times during a 5-month follow-up period. It was demonstrated that MR is superior to CSF and VEP findings in establishing cerebral alterations in MS. A relationship between the results of CSF and VEP examinations and the MR results could not be detected. Negative CSF and VEP results corresponded to positive MR imaging and vice versa. In our series, five negative MR results were obtained in patients with clinically proved MS. The extent of alterations shown up by MR corresponds to the duration of the disease; in particular, more confluent abnormalities in the periventricular region were found in patients with long-standing disease. More plaques were found in patients with a primary relapsing/remitting course of the disease than with the primary chronic progressive form. The clinical course and the grade of disability did not correspond to differences in MR imaging. Follow-up demonstrated that most lesions remain unchanged (72-79%); increases and decreases in the size of the plaques seem to depend on the clinical course. These results suggest that MR is the most sensitive technique for establishing the diagnosis of MS.